REVITALIZATION OF TEUNGKU CHIK PANTE KULU TOMB IN LAM LEOT, KUTA COT GLIE SUB-DISTRICT, ACEH BESAR DISTRICT: REVITALISASI MAKAM TEUNGKU CHIK PANTE KULU DI GAMPONG LAM LEOT KECAMATAN KUTA COT GLIE KABUPATEN ACEH BESAR - Adiba, Fanny (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2023)
This study aims to examine the revitalization of Teungku Chik Pante Kulu's tomb. He is a cleric in Aceh and the author of Hikayat Prang Sabi, a saga that sparked the spirit of the Acehnese in the war against the Dutch. Apart from the manuscript, his existence can be proven through his grave, which is in the village of Lam Leot, Kuta Cot Glie Subdistrict, Aceh Besar District. The results of the study found that this tomb dates from 1836. His grave is marked by a plain tombstone and has been renovated so that it no longer displays the characteristics of an ancient tomb. Through this study, it is known that the way to revitalize this grave is by promoting the role and contribution of Teungku Chik Pante Kulu in defending Aceh from the Dutch. This method is considered very effective because it can increase public knowledge so that the tomb of Tengku Chik Pante Kulu becomes a historical tourist destination in Aceh. The existence of the tomb is also a source of historical, archaeological, and cultural knowledge for the next generation.